The potential of ornamental plant, Sansevieria trifasciata to inhibit the growth of harmful algal bloom species - Mohd Suberi, Ima Amirah; Mohammad Noor, Normawaty; Darnis, Deny Susanti; Mukai, Yukinori; Usup, Gires (International Society for Applied Life Sciences Publishing, 2014)
Malaysia is one of the countries that have been affected by harmful algal bloom (HAB); a phenomena that caused human health problems such as seafood poisoning and loss to aquaculture industries. In Peninsular Malaysia, several HAB problems have been reported since 1991. Many studies have shown that compounds extracted from plants have a promising result to mitigate HAB problems. Unfortunately, this type of study is very limited in Malaysia. Therefore in this study, the potential of ornamental plant; S. trifasciata to inhibit the growth of HAB species i.e. A. tamiyavanichii and A. tamarense was evaluated. The crude extracts of this plant which were obtained from fresh and dried materials were tested on these HAB species at different concentrations (0.5, 1, 1.5, 2 and 2.5 mg/mL). Result showed that all concentrations tested inhibited the growth of both HAB species. The highest removal efficiencies for A. tamiyavanichii using fresh and dried plants were 47.33% at concentration of 0.5 mg/mL and 37.53% at concentration of 1.0 mg/mL, respectively. For A. tamarense, the highest removal efficiency for both fresh and dried plants were 51.59% and 54.83%, respectively, at concentration of 1.5 mg/mL. After 24 hours, all cells in every treatment died whereas cells in control were still active. This shows that S. trifasciata have the potential to be used to mitigate HAB but further studies are needed to refine the findings.